The Role of Information Technology in Encouraging Strategic Management Innovation - Suharto, Suharto (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2023)
The development of information technology has had a significant impact on the way organizations manage and design their business strategies. This research aims to investigate the role of information technology in driving strategic management innovation in various organizations. This research uses a qualitative approach with descriptive methods. The results of this research show that the role of information technology in encouraging innovation in strategic management has a significant positive impact. The integration of information technology in business strategy opens up opportunities for increased operational efficiency, deeper understanding of the market, and flexibility in dealing with changes in the business environment. The application of predictive analysis and artificial intelligence contributes to forecasting market trends and identifying new opportunities, while cloud computing technology supports scalability and flexible access to computing resources. Data protection and information security through information technology are crucial elements in building customer trust. Overall, the results of this research confirm that the integration of information technology not only increases a company's competitiveness, but also creates an environment that supports sustainable innovation in strategic management.Role